2021
DOI: 10.1177/15356841211012483
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Seeking Shelter for Renters With Discrediting Background Records

Abstract: This study illuminates an understudied pathway through which disadvantage is reproduced in the rental housing market: the housing search, application, and tenant screening process. Using in-depth interviews with 25 housing-seekers with criminal conviction records, past evictions, and damaged credit histories, this article examines the direct role of the rental housing search and application process in reproducing economic precarity and social disadvantage among renters with discrediting background records, bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Indeed, a great deal of research has revealed how policy interventions with the stated goal of increasing choice within markets have the unintended consequences of consolidating the power of private service providers (Centeno and Cohen 2012; Hacker 2002; Rich and Jennings 2015; Young and Chen 2020; see also Merton 1936). This is especially pronounced in housing markets where consumers are usually unaware of the full range of housing options available to them (Besbris 2020; Krysan and Crowder 2017), landlords exercise a great deal of discretion in to whom they lease their available housing units (Garboden and Rosen 2018b; Reosti 2021), and renters seek housing under various constraints (DeLuca and Jang-Trettien 2020; DeLuca, Wood, and Rosenblatt 2019; Harvey et al 2020).…”
mentioning
confidence: 99%
“…Indeed, a great deal of research has revealed how policy interventions with the stated goal of increasing choice within markets have the unintended consequences of consolidating the power of private service providers (Centeno and Cohen 2012; Hacker 2002; Rich and Jennings 2015; Young and Chen 2020; see also Merton 1936). This is especially pronounced in housing markets where consumers are usually unaware of the full range of housing options available to them (Besbris 2020; Krysan and Crowder 2017), landlords exercise a great deal of discretion in to whom they lease their available housing units (Garboden and Rosen 2018b; Reosti 2021), and renters seek housing under various constraints (DeLuca and Jang-Trettien 2020; DeLuca, Wood, and Rosenblatt 2019; Harvey et al 2020).…”
mentioning
confidence: 99%
“…3 The experience of racialized dispossession in housing-the loss of physical home through eviction or foreclosure (Desmond and Kimbro, 2015;Rugh, 2015) or the loss of control, autonomy, or sense of self when searching for or seeking to maintain access to secure housing (e.g. Reosti, 2021), both of which disproportionately harm people of color-has devastating consequences. These consequences extend far beyond the realm of housing, contributing to racialized inequalities in multiple spheres, including socioeconomic status and wealth, health, and education (Bachelder et al, 2016;Connolly, 2014;Dantzler, 2021;Desmond and Kimbro, 2015;Korver-Glenn et al, 2023;Krysan and Crowder, 2017;Ladner, 1971;Reosti, 2021;Rugh, 2015;Taylor, 2019).…”
Section: Racialized Dispossession In Us Housingmentioning
confidence: 99%
“…Reosti, 2021), both of which disproportionately harm people of color-has devastating consequences. These consequences extend far beyond the realm of housing, contributing to racialized inequalities in multiple spheres, including socioeconomic status and wealth, health, and education (Bachelder et al, 2016;Connolly, 2014;Dantzler, 2021;Desmond and Kimbro, 2015;Korver-Glenn et al, 2023;Krysan and Crowder, 2017;Ladner, 1971;Reosti, 2021;Rugh, 2015;Taylor, 2019).…”
Section: Racialized Dispossession In Us Housingmentioning
confidence: 99%
See 2 more Smart Citations